Conceptualising a role for the common law in environmental protection in Singapore - CHNG, Kenny (Institutional Knowledge at Singapore Management University, 2021)
In Singapore, the key institutions driving environmental protection are the legislature and the executive. The judiciary’s role in environmental protection has thus far been relatively minor. By drawing upon environmental law theory and comparative analysis of other common law jurisdictions, this paper aims to explore avenues through which the common law can be engaged more meaningfully to further environmental protection in Singapore. A conceptualisation of environmental law as directed at furthering the rule of law by promoting carefully-considered and participatory environmental governance will be suggested as a fruitful way forward for thinking about the role of the common law in environmental protection. Drawing upon this theory, as well as the experience of other common law jurisdictions, the paper will propose a set of concrete steps by which greater common law engagement with environmental protection in Singapore can be achieved.